Field of dreams [videorecording (DVD)] - Robinson, Phil Alden; Costner, Kevin; Madigan, Amy; Jones, James Earl; Liotta, Ray; Lancaster, Burt, 1913-1994; Kinsella, W. P. (Universal Home Video, 1998)
Ray Kinsella (Kevin Costner) hears a voice, followed by a brief vision of a baseball field. He believes that if he builds a baseball diamond in his cornfield, Shoeless Joe Jackson from the infamous 1919 Chicago "Black" Sox will return to play baseball. By being willing to take a chance, Ray gets a second time up at bat in life.